Instytucjonalne fundamenty polityki promocji gospodarki Polski - Górski, Jarosław Wojciech (The promotional policy of Poland's economy - the institutional basis, 2006)
The article deals with the problem of the policy of promoting Poland’s economy. The aim of the text is to analyse the institutional environment of the policy with respect to the efficiency of the introduced solutions and prospects for further development. Especially, some connections of the promotional policy of economy with the overall promotional policy of a country are showed. Futhermore, the analysis focuses on the relationships within the network of promotional organizations that occur between governmental and non-govemmental institutions. The text offers also an inspection of relations of substitution and complementarity which arise among different functions and actions of various institutions which deal with the promotion of Polish economy. The general conclusion from the research is that there is a great need fora closer coordination of a big numer of different programs in the field of promotional policy. A clear relationship net between instututions should be established, especially between agencies managing overall policy of Poland’s promotion and those responsible for economic promotion. It is also recommended that more intensive efforts should be made in order to found a strong body in charge of economic promotional policy - supposedly the Polish Agency for Economic Promotion (Polska Agencja Promocji Gospodarczej - PAPG).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 379-391